Proses Kerja dan Tata Kelola Birokrasi di Sekretariat DPRD Provinsi Jawa Barat - Aden Herdiana (Fisip UIN Sunan Gunung Djati Bandung, 2024)
This article aims to find out how the work process, strategy implemented by the Secretary of the West Java Provincial DPRD in improving the efficiency of work processes and bureaucratic governance, The main focus of this strategy is an in-depth analysis of existing workflows, the application of information technology for automation and digitalization, human resource development, effective financial management, and compliance with applicable regulations and policies. The method used in this study is a qualitative method with the data collection process carried out by means of document studies, interviews, direct observation and document studies that can help the running of this research process. With 3 informants as employees at the Secretariat of the West Java Provincial DPRD. So by implementing this strategy, it is hoped that a faster, more efficient, and transparent work process can be created, as well as better bureaucratic governance. This article also highlights the importance of effective communication of teamwork in achieving common goals to improve organizational performance. The results and implementation of this strategy are expected to improve services to the community and strengthen accountability and transparency in the management of public administration.